Answer:
2(x - 6)(2x + 3)
Explanation:
There are a few steps to factoring depending on the polynomial.
Step 1. Factor our a common factor if possible.
Every term is divisible by 2, so factor out a 2.
4x^2 - 18x - 36 =
= 2(2x^2 - 9x - 18)
Step 2. We need to factor the quadratic trinomial.
Now we have a quadratic trinomial, in which the x^2 term is not plain x^2, but it has a coefficient of 2.
Our polynomial is of the form ax^2 + bx + c, with "a" not equal to 1.
We have 2x^2 - 9x - 18, so we have a = 2, b = -9, c = -18.
We can try guessing, but instead, I will use the "ac" method.
Step A. Multiply coefficients ac:
ac = 2(-18) = -36
Step B. Now we need two numbers that add to b and multiply to ac.
We need two numbers that add to -9 and multiply to -36.
The numbers are -12 and 3 since (-12)(3) = -36, and -12 + 3 = -9.
We now break up the middle term, -9x, using these two numbers.
= 2(2x^2 - 12x + 3x - 18)
Now we factor by grouping. Factor a common factor out of the first two terms, and factor a common factor out of the last two terms.
= 2[2x(x - 6) + 3(x - 6)]
x - 6 is a common factor inside the brackets, so we factor it out inside the brackets.
= 2[(x - 6)(2x + 3)]
= 2(x - 6)(2x + 3)